Chimeric 6‐methylsalicylic acid synthase with domains of acyl carrier protein and methyltransferase from Pseudallescheria boydii shows novel biosynthetic activity - Liao, Ji‐Long (Microb Biotechnol, 2019)
Polyketides are important secondary metabolites, many of which exhibit potent pharmacological applications. Biosynthesis of polyketides is carried out by a single polyketide synthase (PKS) or multiple PKSs in successive elongations of enzyme‐bound intermediates related to fatty acid biosynthesis. The polyketide gene PKS306 from Pseudallescheria boydii NTOU2362 containing domains of ketosynthase (KS), acyltransferase (AT), dehydratase (DH), acyl carrier protein (ACP) and methyltransferase (MT) was cloned in an attempt to produce novel chemical compounds, and this PKS harbouring green fluorescent protein (GFP) was expressed in Saccharomyces cerevisiae. Although fluorescence of GFP and fusion protein analysed by anti‐GFP antibody were observed, no novel compound was detected. 6‐methylsalicylic acid synthase (6MSAS) was then used as a template and engineered with PKS306 by combinatorial fusion. The chimeric PKS containing domains of KS, AT, DH and ketoreductase (KR) from 6MSAS with ACP and MT from PKS306 demonstrated biosynthesis of a novel compound. The compound was identified with a deduced chemical formula of C(7)H(10)O(3), and the chemical structure was named as 2‐hydroxy‐2‐(propan‐2‐yl) cyclobutane‐1,3‐dione. The novel compound synthesized by the chimeric PKS in this study demonstrates the feasibility of combinatorial fusion of PKS genes to produce novel polyketides.